Validation of the IDF-DAR risk assessment tool for Ramadan fasting in patients with diabetes in primary care - Baynouna Alketbi, Latifa; Afandi, Bachar; Nagelkerke, Nico; Abdubaqi, Hanan; Al Nuaimi, Ruqaya Abdulla; Al Saedi, Mariam Rashed; Al Blooshi, Fatima Ibrahim; Al Blooshi, Noura Salem; AlAryani, Aysha Mohammed; Al Marzooqi, Nouf Mohammed; Al Khouri, Amal Abdullah; Al Mansoori, Shamsa Ahmed; et al. (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionIn patients with diabetes intending to fast, Ramadan, risk assessment, and stratification are essential for an individualized treatment plan. It seems that the new IDF-DAR risk stratification tool (International Diabetes Federation - Diabetes and Ramadan Alliance) has become the primary tool in this setting. This study aims to validate this tool in the Abu Dhabi population.MethodThe assessment was performed before Ramadan, followed by an evaluation of any significant outcome after Ramadan through tele-interview and an electronic medical records review. Patients were included if the attending physicians used the tool in the risk assessment of the patients within 6 weeks before Ramadan 1,444 (CE 2022) in the AHS healthcare center.ResultsThe study included 435 patients. Half (51.7%) were in the low-risk category of the IDF-DAR risk stratification tool, 28.5% were in the moderate-risk category, and 19.8% were in the higher-risk category. Of the total patients, 81.3% fasted during the entire Ramadan period and 18.7% attempted to fast. A total of 14 (3.8%) patients were admitted at least once, and 56 (12.9%) had at least one significant event, including admission to the hospital. Using univariable logistic regression, the occurrence of adverse events was significantly associated with more days not fasted, B = −0.126, p < 0.001, OR = 0.88 (0.839–0.927). Using multivariable logistic regression, and after controlling for all variables studied, other risk factors identified with the occurrence of adverse events in this study were as follows: being in the low-risk category of the DAR risk assessment tool, B = −1.1, OR = 0.34 (0.157–0.744), p = 0.0072; being in the frail category compared to the reference category, the robust category, B = 1.54, OR = 4.6 (1.3–16.6), p = 0.018; and older age B = −0.034, OR = 0.966 (0.938–0.995). There was no significant difference between moderate- and high-risk categories in the occurrence of significant adverse events (SAEs). Similar determinants of fasting were identified during the entire Ramadan period using multivariable logistic regression.ConclusionAccording to the IDF-DAR risk assessment, patients with diabetes in the low-risk category had a better outcome than those in the moderate- or high-risk categories regarding SAEs. Another independent risk factor is if the patient is frail, according to the FRAIL scoring.